An evaluation of the use of ronidazole for the treatment of Tritrichomonas foetus in cats - Morgan, Genever Bethan (Veterinary Evidence, 2019)
PICO question In cats infected with Tritrichomonas foetus, does treatment with oral ronidazole compared to an alternative antiprotozoal treatment or placebo result in successful resolution of clinical signs and eradication of disease? Clinical bottom line Ronidazole use appears to be efficacious in eradicating infection with Tritrichomonas foetus and resolving diarrhoea associated with infection. A dose range of 30–50 mg/kg 12–24 hourly has been suggested, with evidence suggesting that a dose of 30 mg/kg 24 hourly for 14 days may be effective. However, some cats may require higher doses and some may not respond to treatment, and relapse may occur during a protracted period following completion of the treatment course. Neurological side effects appear to be uncommon but may occur with doses of 30 mg/kg and above. A total of six studies are reviewed: Three randomised, controlled studies, one cohort study and two case series (one retrospective). Findings indicate efficacy of ronidazole treatment in eradicating infection and resolving diarrhoea, however many studies involved small sample sizes and limited follow-up. Therefore, evidence to support the use of ronidazole in Tritrichomonas foetus infected cats remains relatively limited.